Do Different Legal System and self-referral Pathways Influence Relationship Violence Intervention Program Success? - Evans, Catherine P. (Journal of family violence, 2024)
PurposePrior studies have found that court-referred individuals are more likely to complete relationship violence intervention programs (RVIP) than self-referred individuals. The current study provides a more nuanced analysis by examining whether RVIP clients referred through various legal and non-legal pathways (Probation, Deferred Prosecution, Civil Court, Court Case Pending, or No Court Involvement) have differential program attendance or post-program recidivism. MethodsArchival data on referral pathways and program attendance were examined for 879 men who presented for services at a community-based RVIP, and post-program recidivism was examined for a subset of cases (n = 392). ResultsIndividuals with any type of court order were 1.9 times more likely than those with no court involvement to complete the intervention program. Individuals with court cases pending were somewhat less likely than court-referred cases to complete the intake process, but significantly more likely than those with no court involvement to complete the program. Criminal recidivism during the two-years after scheduled program completion did not differ significantly by referral pathway. The data also revealed social disparities in referral pathways. Black individuals and those with less than high school education were more likely to be on probation, whereas white individuals and those with post-secondary education were more likely to have no court involvement. ConclusionsThe findings support the use of legal referral pathways that can limit the negative impacts of carceral system involvement while highlighting the need for better strategies to engage and retain RVIP clients who have no court involvement.